PENINGKATAN AKTIVITAS BELAJAR SISWA SD PADA PEMBELAJARAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN MEDIA GAMBAR BERSERI - Sari, Novita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract The purpose of this research is to describe the increase of student learning activity on writing descriptive composition learning using beamed image media V B grade 54 school west pontianak. This research methad used is descriptive methad. The subjects in this research is student of V B class who numbered 35 people. The research result showed that the physic activity in cycle I was 63.33% , in cycle II the average score was 76.78% , and the cycle III the average score was 77.41%. The mental activity in cycle I the average score was 8.33% , cycle II the average score was 22.31% , and cycle III the average score was 35.47%. The emotional activity in cycle I the average score was 51.66% , cycle II the average score was 55.35% , and cycle III the average score was 59.67%. Based on the data analisys of student learning activity, shows that by using beamed image media can increase the student learning activity. Keywords: Improvement, Activity, Descriptive Composition, Beamed Image Media